Lipid biomarkers provide evolutionary signposts for the oldest known cases of tuberculosis. (June 2015) - Lee, Oona Y-C.; Wu, Houdini H.T.; Besra, Gurdyal S.; Rothschild, Bruce M.; Spigelman, Mark; Hershkovitz, Israel; Bar-Gal, Gila Kahila; Donoghue, Helen D.; Minnikin, David E.
Summary: Studies on the evolution of tuberculosis, and the influence of this disease on human and animal development and interaction, require the accumulation of indisputable biomarker evidence. Ideally, the determination of full genomes would provide all the necessary information, but for very old specimens DNA preservation may be compromised and only limited DNA amplification may be a possibility. Mycobacterium tuberculosis is characterised by the presence of unusual cell envelope lipids, with specific biomarker potential. Lipid biomarker recognition has been decisive in pinpointing the oldest known cases of human and animal tuberculosis; the former are a woman and child from a pre-pottery settlement at Atlit-Yam, Israel (∼9, 000 ka) and the latter is an extinct Bison antiquus from Natural Trap Cave, Wyoming (∼17, 000 ka). Including some new data, it is demonstrated how analysis of a combination of mycolic, mycocerosic and mycolipenic acid and phthiocerol biomarkers provide incontrovertible evidence for tuberculosis in these landmark specimens.